Pengaruh Pelatihan Aparatur Desa, Ketersediaan Fasilitas Teknologi dan Pendampingan Pemerintah terhadap Akuntabilitas Pengelolaan Dana Desa di Kecamatan Ponrang Selatan - Hijerah, Nur; Sahrir, Sahrir; Patra, Andi Dahri Adi (Universitas Syiah Kuala, 2025)
Village fund management has become a crucial issue in Indonesia's rural development agenda, particularly following the enactment of Law No. 3 of 2024 on Village Fund Management, which mandates transparent and accountable financial governance. However, implementation challenges persist, including delayed financial reporting, limited transparency, and suspected fund misuse, particularly in South Ponrang District. This study aims to comprehensively examine the influence of village apparatus training, technology facility availability, and government assistance on village fund management accountability using a quantitative approach. The research employed an associative-causal design with a saturated sampling technique, involving 58 respondents comprising village heads, secretaries, treasurers, and staff involved in village financial management in South Ponrang District, Luwu Regency, South Sulawesi. Data were collected through structured questionnaires and analyzed using descriptive statistics, validity and reliability tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. The findings reveal that technology facility availability and government assistance have significant positive effects on village fund management accountability, while village apparatus training shows no significant influence. The regression model explains 96.4% of accountability variations with an R value of 0.964. The study concludes that investment in technological infrastructure such as computers, Siskeudes applications, and internet access, combined with intensive government assistance programs, are key factors in enhancing transparency and accountability in village fund management, while formal training programs require substantial evaluation and improvement